2014
DOI: 10.3109/09540261.2014.924909
|View full text |Cite
|
Sign up to set email alerts
|

Workplace spirituality as a moderator in relation between stress and health: An exploratory empirical assessment

Abstract: The present study explores the role of workplace spirituality in moderating the relationship between occupational stress and the health of managerial personnel in India. A sample of 150 managers working in different public and private organizations was used to measure workplace spirituality, occupational stress, and health using the Spirituality at Work scale, the Occupational Stress Index and the 28-item General Health Questionnaire, respectively. The findings reveal that workplace spirituality moderates the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 27 publications
3
38
0
2
Order By: Relevance
“…Numerous studies have shown that Christian and non-Christian prayer can have beneficial effects. An Indian research study revealed that workplace spirituality moderates the negative relationship of stress and health, and positively correlates with health (Kumar and Kumar, 2014). Benevene and Fiorilli (2015) comparing burnout of Catholic consecrated teachers with lay teachers from Italian public and Catholic schools pointed out that teachers from public schools obtained higher means on the emotional exhaustion and depersonalization dimensions (Benevene and Fiorilli, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that Christian and non-Christian prayer can have beneficial effects. An Indian research study revealed that workplace spirituality moderates the negative relationship of stress and health, and positively correlates with health (Kumar and Kumar, 2014). Benevene and Fiorilli (2015) comparing burnout of Catholic consecrated teachers with lay teachers from Italian public and Catholic schools pointed out that teachers from public schools obtained higher means on the emotional exhaustion and depersonalization dimensions (Benevene and Fiorilli, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A few isolated examples of workplace spirituality serving as mediator or moderator in models of the relationships between other variables (e.g. Kumar and Kumar 2014) are now beginning to appear, indicating that the construct's development continues to progress.…”
Section: Conclusion and Directions For Future Researchmentioning
confidence: 97%
“…From the worker point of view, maintaining productivity requires a self-motivation effort that goes beyond financial rewards [5,6]. In order to support employees in this motivational task, organizations are making efforts with different approaches [7,8]. One of these approaches has been discussed in the organizational changes literature as workplace spirituality, which was defined as "the recognition that employees have an inner life that nourishes and is nourished by meaningful work than takes place in the context of community" [9,10].…”
Section: Introductionmentioning
confidence: 99%